Small island tourism: Future investment or environmental time bomb? A comparative study of Cempedak Private Island and Funtasy Island - Suriwahyudi; Nugraha, Awaludin; Hadian, Mohamad Sapari Dwi (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
The development of private islands as luxury tourism destinations is expanding in Indonesia, particularly in the Riau Islands. This qualitative research uses a comparative case study method to examine two private island projects (Cempedak Private Island and Funtasy Island) to assess whether private island development constitutes a sustainable investment or poses an environmental threat. Primary data were collected through interviews with stakeholders and supported by document analysis. Findings show that Cempedak Island successfully implemented eco-tourism principles through strong governance and local community involvement, while Funtasy Island suffered from mismanagement, regulatory issues, and ecological degradation. The analysis, framed using the ESG (Environmental, Social, Governance) perspective, reveals the significance of inclusive planning, sustainable architecture, and transparent leadership in ensuring long-term viability. The study provides insights for investors, policymakers, and scholars, although its findings are context-specific and may not be generalizable to all private island developments. Future research is needed to test the ESG framework across diverse geographic and regulatory environments.